A Liquid Hydrogel to Restore Long Term Corneal Integrity After Perforating and Non-Perforating Trauma in Feline Eyes - Juarez, Alejandro; Djallali, Mohamed; Piché, Marilyse; Thériault, Mathieu; Groleau, Marc; Beroual, Sharifa; McTiernan, Christopher D.; Lin, Grace; Hélie, Pierre; Carrier, Michel; Griffith, May; Brunette, Isabelle (Frontiers in Bioengineering and Biotechnology, 2021)
Purpose: To evaluate long-term in vivo functionality of corneas regenerated using a cell-free, liquid hydrogel filler (LiQD Cornea) after deep corneal trauma in the feline model. Methods: Two healthy cats underwent 4 mm diameter stepwise 250/450 µm deep surgical corneal ablation with and without needle perforation. The filler comprising 10% (w/w) collagen-like peptide conjugated to polyethylene glycol (CLP-PEG) and 1% fibrinogen and crosslinked with 2% (w/w) 4-(4,6-dimethoxy-1,3,5-triazin-2-yl)-4-methylmorpholinium chloride (DMTMM), was applied to the wound bed previously coated with thrombin (250 U/ml). In situ gelation occurred within 5 min, and a temporary tarsorrhaphy was performed. Eyes were examined weekly for 1 month, then monthly over 12 months. Outcome parameters included slit-lamp, Scheimpflug tomography, optical coherence tomography, confocal and specular microscopy, and immunohistochemistry studies. Results: The gelled filler was seamlessly incorporated, supporting smooth corneal re-epithelialization. Progressive in-growth of keratocytes and nerves into the filler corresponding to the mild haze observed faded with time. The regenerated neo-cornea remained stably integrated throughout the 12 months, without swelling, inflammation, infection, neovascularization, or rejection. The surrounding host stroma and endothelium remained normal at all times. Tomography confirmed restoration of a smooth surface curvature. Conclusion: Biointegration of this hydrogel filler allowed stable restoration of corneal shape and transparency in the feline model, with less inflammation and no neovascularization compared to previous reports in the minipig and rabbit models. It offers a promising alternative to cyanoacrylate glue and corneal transplantation for ulcerated and traumatized corneas in human patients.